Electroacoustic system in the National Museum "Panorama Racławicka" in Wrocław - J. BEDNAREK; T. GUDRA; K. RUDNO-RUDZIŃSKI (Archives of Acoustics)
This paper presents a designed and produced electroacoustic system assisting the tour of an exhibition intended for a great number of visitors. The microprocessor operated electroacoustic system fulfills two functions: transfers the commentary to the exhibition and controls the visitor’s traffic. A sound amplification system" which makes it possible to relay at the same time six language versions of the explanatory commentary to different groups of listeners through loudspeakers and earphones" is presented. Such a system enables simultaneous transmission of two different commentaries to two groups in the same interior. Fundamental elements of technological designs applied in the electroacoustic system are also discussed here.